Model and Approach for Loaded Tooth Contact Analysis （LTCA） of Gear Drives - Fang Zongde (Jixie chuandong)
In this paper,on the basis of tooth contact analysis （TCA） considering accurate geometry topology,a model including transmission error,gaps between working tooth surfaces,deformations of gears and their supports for loaded tooth contact analysis （LTCA） of gear drives was established.A corresponding apporoach is presented,which combines the geometrical and mechanical analyses into one and provides the simulating results.